A conceptual framework on modes of governance for the regeneration of Chinese 'villages in the city'. (August 2015) - Lin, Yanliu; Hao, Pu; Geertman, Stan
China's rapid urbanisation has created a special form of urban built environment known as 'village in the city' (ViC). Various governance approaches have been applied to redevelop ViCs, which are prevalent in big cities. However, owing to the specific conditions of ViCs and the diverse contexts of urban development within and across cities, those approaches remain largely case-specific and are hampered by a lack of guiding principles. This article presents a framework on modes of governance to understand the choice of and the differences between modes of governance as well as their positive and negative consequences for the regeneration of ViCs. Case studies of various types of ViC regeneration practices in Guangzhou and Shenzhen are used to illustrate the framework's application. The article concludes that new modes of governance that are interactive, inclusive and collaborative are called for to achieve the sustainable regeneration of ViCs.